2013
DOI: 10.1002/adfm.201302463
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Small Iron Oxide Doped Polypyrrole Nanoparticles for In Vivo Multimodal Imaging Guided Photothermal Therapy

Abstract: Recently, near‐infrared (NIR) absorbing conjugated polymeric nanoparticles have received significant attention in photothermal therapy of cancer. Herein, polypyrrole (PPy), a NIR‐absorbing conjugate polymer, is used to coat ultra‐small iron oxide nanoparticles (IONPs), obtaining multifunctional IONP@PPy nanocomposite which is further modified by the biocompatible polyethylene glycol (PEG) through a layer‐by‐layer method to acquire high stability in physiological solutions. Utilizing the optical and magnetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
147
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(147 citation statements)
references
References 44 publications
(17 reference statements)
0
147
0
Order By: Relevance
“…Very recently, a number of groups including ours have reported that NIR-absorbing supramolecular nanomaterials serve as strong photothermal agents, showing excellent cancer ablation effect both in vitro and in vivo. [12,21,57] Our group demonstrated highly stable and biocompatible supramolecular adducts of SQ and the natural carrier protein, i.e., bovine serum albumin (BSA) (SQ⊂ BSA) for tumor photothermal therapy in vivo ( Figure 10a). [57] SQ was selectively bound to BSA hydrophobic domain via hydrophobic and hydrogen bonding interactions and showed up to 80-fold enhanced fluorescence intensity (Figure 10b).…”
Section: Photothermal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a number of groups including ours have reported that NIR-absorbing supramolecular nanomaterials serve as strong photothermal agents, showing excellent cancer ablation effect both in vitro and in vivo. [12,21,57] Our group demonstrated highly stable and biocompatible supramolecular adducts of SQ and the natural carrier protein, i.e., bovine serum albumin (BSA) (SQ⊂ BSA) for tumor photothermal therapy in vivo ( Figure 10a). [57] SQ was selectively bound to BSA hydrophobic domain via hydrophobic and hydrogen bonding interactions and showed up to 80-fold enhanced fluorescence intensity (Figure 10b).…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Meanwhile, by emerging the modern nanoscience and biotechnology, a new research field of supramolecular nanosystems has been gradually developed which attracts wide attentions for biomedicine. [1][2][3][4][5][6][7] Supramolecular self-assembled nanosystems used as diagnostic/therapeutic agents encompass a wide range of substances, such as liposomes, [8][9][10][11] polymer-based nanoparticles, [12][13][14][15][16][17] carbon nanomaterials, [18][19][20][21] metallic nanomaterials [22][23][24][25] and zeolites. [26][27][28][29] Supramolecular self-assembled nanosystems can provide clear signals such as fluorescent, magnetic, photoacoustic signals for imaging when acting on lesion location as bioprobes.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging-guided PTT was accomplished with IONP@PPy-PEG NPs [152]. Ultrasmall iron oxide nanoparticles (IONPs) were coated with polypyrrole (PPy), a NIR-absorbing CP, followed by further layer-by-layer (LBL) coating with polyallylamine hydrochloride (PAH) and polyacrylic acid (PAA).…”
Section: Nanoplatforms For Multimodal Imaging and Therapymentioning
confidence: 99%
“…In recent years, a large variety of NIR-absorbing inorganic nanomaterials, such as different noble metal (e.g. Au, Ag, Pt) nanostructures [8][9][10][11][12][13], carbon nanomaterials [3,4,6,7,14], as well as transition metal sulfide or oxide nanoparticles [15][16][17][18][19][20][21], have been widely explored by many research teams including ours as photothermal agents for PTT ablation of cancer in vitro and in vivo. Despite the high therapeutic efficacy obtained in many pre-clinical animal models, the non-biodegradable nature and Nano Res.…”
Section: Introductionmentioning
confidence: 99%